TERRA and the state of the telomere - Rippe, Karsten; Luke, Brian (Nature structural & molecular biology, 2015)
Transcription of telomeres generates long noncoding RNAs (lncRNAs) composed of telomeric repeat sequences (TERRA) that hybridize with telomeric DNA and are components of telomeric heterochromatin. This Perspective considers the physiological roles of TERRA in telomere homeostasis and proposes that TERRA's functions are determined by the state of its telomere targets.
Gesehen am 25.06.2020